Multı-Method Analysıs On Vıdeo Game Addıctıon And Academıc Motıvatıon Among College Student In Batam: A Case Of Genshın Impact - Ricky Hartanto; Mangapul Siahaan (CoMBInES - Conference on Management, Business, Innovation, Education and Social Sciences, 2023)
Online games are a new lifestyle for all ages. The presence of online games is now possible with the many internet cafes (warnet) in cities and rural areas. There is a fairly large community for the Genshin Impact game itself. Factors contributing to this explosion of the global video game community of games. Some claim that the main reason Genshin Impact is so famous is its open-world RPG style of play, which allows players to explore Teyvat (the world in Genshin Impact) freely without worrying about running out of locations to explore. This research was conducted with the aim of knowing the impact of Genshin Addiction on motivation, social anxiety, loneliness among students in the city of Batam. The method in this study uses quantitative and qualitative with techniques for distributing questionnaires from Google Forms to Batam city students and interviews also data analysis using IBM SPSS Statistics 25 and SmartPLS. The results of the quantitative research show that the variables of social anxiety and loneliness have a positive effect on genshin addiction. The qualitative results show that some respondents still feel anxious and lonely when playing genshin games. From this study, genshin addiction does not have a significant relationship with motivation. Meanwhile, genshin addiction has a significant relationship with social anxiety and loneliness. Therefore, from these findings it is suggested to reduce or limit playing Genshin Impact and try to do positive activities.